Love Conflict Reflected In Jennifer Crusie's Anyone But You Novel (1996): Psychoanalytic Approach - Kusaeri, Akhmad, Dr. Phil. Dewi Chandraningrum, M. Ed, Titis Setyabudi, S.S. M. Hum (2015)
The major problem of this study is love conflict which is undergone by Nina Askew, because Guy, her ex husband with his job is more importance than Nina. Nina is bored and feels lonely. She asks to divorce with guy. Then Nina's dog (Fred) brings her to Alex. Alex feels interested on her. When Guy is bankrupts, he wants reconcile with Nina. Alex comes at Nina's apartment and admits as Nina's boyfriend. Conflict arises and Alex has success saves Nina of disturbing Guy. Nina feels free and she knows that Alex has great love. Thus conflict occurs when Nina realizes that she is older ten years than Alex. The objective of this study is to analyze Jennifer Crusie's Anyone but You Novel (1996) on the structural elements and analyze this novel based on the Psychoanalytic Approach. The Researcher employs qualitative method. The researcher uses two data sources: primary and secondary. The primary data source is about Anyone but You (1996) novel itself. Then, the secondary data sources are the books about psychoanalysis, references from internet about Anyone but You, journals and other sources, which have relation to the analysis. The method of data collection is library research and the technique of data collection is descriptive technique. Based on the analysis, the researcher gets some conclusions. The study shows that the problem which is faced by the major character is failness in getting her whole affection from her ex husband. It causes she wants to get freedom, the whole affection and go away for getting the true love although, she undergoes difficultness with her body and her old that Nina is older than Alex Moore but they can show a good relationship finally, they married happily. Keywords: Love Conflict and Psychoanalytic approach